2007
DOI: 10.1017/s1751731107683803
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake and performance of growing lambs raised on concentrate-based diets under cafeteria feeding systems

Abstract: Two trials were undertaken to study the effects of cafeteria feeding systems on the feed intake, animal performance and carcass characteristics of growing lambs. Trial 1 was designed to compare conventional and cafeteria feeding systems in terms of the growth of individually reared lambs. For this assay, 26 weaned Merino lambs (15.5^0.20 kg live weight) were assigned to three dietary treatment groups: (1) a control group fed barley straw and commercial concentrate under a conventional feeding system, (2) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
13
1
1
Order By: Relevance
“…These findings support the idea that lambs offered a choice among an option of feeds (ground barley, cottonseed meal, wheat bran and alfalfa hay) successfully regulated their nutrient intakes and attained better growth performance (Görgülü et al, 1996;Dikmen et al, 2009). However, the results do not confirm that cafeteria or FCF reduces the feed intake of lamb, as it can balance its nutrient requirement well (Sahin et al, 2003;Askar et al, 2006;Rodríguez et al, 2007;Dikmen et al, 2009;Kaya, 2011). These results indicate that the intake regulation mechanism is most probably not specific for BtW of lambs, but it may change when animals are free to choose when and what to eat, or if chemical composition allow them meeting nutritional requirements of the animals (Fedele et al, 2002;Dikmen et al, 2009).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…These findings support the idea that lambs offered a choice among an option of feeds (ground barley, cottonseed meal, wheat bran and alfalfa hay) successfully regulated their nutrient intakes and attained better growth performance (Görgülü et al, 1996;Dikmen et al, 2009). However, the results do not confirm that cafeteria or FCF reduces the feed intake of lamb, as it can balance its nutrient requirement well (Sahin et al, 2003;Askar et al, 2006;Rodríguez et al, 2007;Dikmen et al, 2009;Kaya, 2011). These results indicate that the intake regulation mechanism is most probably not specific for BtW of lambs, but it may change when animals are free to choose when and what to eat, or if chemical composition allow them meeting nutritional requirements of the animals (Fedele et al, 2002;Dikmen et al, 2009).…”
Section: Resultsmentioning
confidence: 59%
“…A cafeteria feeding system or offering free-choice of food (free choice feeding, FCF) may be a practical alternative that offers some advantages over conventional compound feeding of fattening lambs (Fedele et al, 2002;Dikmen et al, 2009). Indeed it has been indicated that sheep, reared in a controlled environment can successfully select a diet of adequate intake from a suitable pair of feeds to match their nutritional requirements and have a feed efficiency and body growth rate similar or better than those achieved with conventional feeding system (FS) (Sahin et al, 2003;Askar et al, 2006;Rodríguez et al, 2007Rodríguez et al, , 2008Dikmen et al, 2009). Behavioural responses such as feeding and welfare behaviours are very important in connection with feed intake and feeding management, since it has direct effects on consumption patterns, feedstuff availability and selection of feeds (Keskin et al, 2004;Kaya, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Keskin et al (2004) observed greater protein intake and decreased energy intake in free-choice fed lambs compared with lambs fed a single ration, which also was associated with a similar performance among treatments. Protein overingestion in ruminants is likely to be related to the maintenance of ruminal homeostasis when ruminants ingest diets high in grain or secondary compounds, both of which can induce acidosis (James et al, 2001;Rodriguez et al, 2007). Acidosis can be prevented by the buffer capacity of ammonia (one of the byproducts of protein degradation) in the rumen (Owens et al, 1998).…”
Section: Dietary Monotony Feed Diversity and Diversity With Plant Tmentioning
confidence: 99%
“…Grasses in each ration were offered individualy to five experimental deers in separate feed throught in a cafetaria system (Babayemi et al, 2006;Farid et al, 2006;Rodriguez et al, 2007). Each grass was offered 2.25 kg at 07.00 and 16.00.…”
Section: Data Collection and Analysismentioning
confidence: 99%